DYNAMICS OF DEVELOPMENT OF INDUSTRIAL SECTORS IN THE REGIONS OF UZBEKISTAN IN THE CONDITIONS OF A GREEN ECONOMY - Fukuda Hiroki (Innovate Conferences, 2025)
This article analyzes the dynamics of the development of industrial sectors in the regions of Uzbekistan in the context of a green economy. The study aims to identify regional differences in improving the environmental and economic efficiency of industrial enterprises, rational use of resources, waste reduction, and the introduction of innovative technologies. The article analyzes the adaptation of the energy, chemical, metallurgical, transport, and agricultural sectors to the requirements of a green economy, development prospects, and regional differences. The article also provides practical recommendations related to environmental sustainability, job creation, and increasing export potential. The results provide a scientific and practical basis for modernizing Uzbekistan's industrial policy and implementing a green transformation.
Keywords: green economy, industrial sectors, regional development, environmental sustainability, energy efficiency, waste recycling, innovative technologies, sustainable jobs, export potential.